A patient-driven registry on Behçet’s disease: the AIDA for patients pilot project - Gaggiano, Carla; Del Bianco, Alessandra; Sota, Jurgen; Gentileschi, Stefano; Ruscitti, Piero; Giacomelli, Roberto; Piga, Matteo; Crisafulli, Francesca; Monti, Sara; Emmi, Giacomo; De Paulis, Amato; Vitale, Antonio; et al. (Frontiers in Medicine, 2023)
Introduction This paper describes the creation and preliminary results of a patient-driven registry for the collection of patient-reported outcomes (PROs) and patient-reported experiences (PREs) in Behçet’s disease (BD). Methods The project was coordinated by the University of Siena and the Italian patient advocacy organization SIMBA (Associazione Italiana Sindrome e Malattia di Behçet), in the context of the AIDA (AutoInflammatory Diseases Alliance) Network programme. Quality of life, fatigue, socioeconomic impact of the disease and therapeutic adherence were selected as core domains to include in the registry. Results Respondents were reached via SIMBA communication channels in 167 cases (83.5%) and the AIDA Network affiliated clinical centers in 33 cases (16.5%). The median value of the Behçet’s Disease Quality of Life (BDQoL) score was 14 (IQR 11, range 0–30), indicating a medium quality of life, and the median Global Fatigue Index (GFI) was 38.7 (IQR 10.9, range 1–50), expressing a significant level of fatigue. The mean Beliefs about Medicines Questionnaire (BMQ) necessity-concern differential was 0.9 ± 1.1 (range – 1.8–4), showing that the registry participants prioritized necessity belief over concerns to a limited extent. As for the socioeconomic impact of BD, in 104 out of 187 cases (55.6%), patients had to pay from their own pocket for medical exams required to reach the diagnosis. The low family socioeconomic status (p < 0.001), the presence of any major organ involvement (p < 0.031), the presence of gastro-intestinal (p < 0.001), neurological (p = 0.012) and musculoskeletal (p = 0.022) symptoms, recurrent fever (p = 0.002), and headache (p < 0.001) were associated to a higher number of accesses to the healthcare system. Multiple linear regression showed that the BDQoL score could significantly predict the global socioeconomic impact of BD (F = 14.519, OR 1.162 [CI 0.557–1.766], p < 0.001). Discussion Preliminary results from the AIDA for Patients BD registry were consistent with data available in the literature, confirming that PROs and PREs could be easily provided by the patient remotely to integrate physician-driven registries with complementary and reliable information.